P016 Constitutive activity of the cation channel TRPM8 regulates monocyte to macrophage transition in humans to control intestinal inflammation. (25th January 2019) - Hornsby, E; Peiris, M; Peiris, M; King, H W; Wing, E S; Lindsay, J O; Blackshaw, L A; Stagg, A J
Abstract: Background: Abnormal intestinal monocyte to macrophage transition plays a critical role in inflammatory bowel disease (IBD). TRPM8 (Transient Receptor Potential Melastatin 8) is a ligand-gated cation channel activated by factors including cold and cooling compounds leading to cation influx. TRPM8 RNA is increased in both the colonic mucosa of Crohn's disease patients and mice with experimentally induced colitis in which activation of TRPM8 with synthetic agonists ameliorates disease. Mice with TRPM8-deficient macrophages develop worse colitis, implying that TRPM8 in macrophages is protective against intestinal inflammation. Our aim was to test the hypothesis that TRPM8 activity controls inflammation in the human intestine by modulating monocyte to macrophage transition. Methods: Blood monocytes from healthy volunteers were differentiated into macrophages using M-CSF, in the presence or absence of TRPM8 antagonist (AMTB) or agonist (icilin). Intestinal CD14+ monocytes were extracted from colonic biopsies obtained from control patients. Flow cytometry was used to measure TRPM8 protein, membrane potential using DISBAC2(3) dye, phagocytosis of fluorescent microspheres, cell viability, and TNF-α production. RNA seq was used to determine differential gene expression. Results: TRPM8 protein was detected in blood monocytes, in vitro derived macrophages and CD64+ monocyte/macrophages in the intestinal mucosa. Inhibition, but not activation of TRPM8 activity in blood monocytes resulted in membrane depolarisation after 3 h, which was associated with increased cell survival ( p = 0.0001) and enhanced production of LPS-induced TNF-α ( p = 0.0001, Figure 1) after 24 h. Inhibition of TRPM8 also enhanced TNF-α production by CD14+ intestinal monocytes. Macrophages generated from blood monocytes in the presence of AMTB had reduced phagocytic capacity ( p = 0.03) and differential expression of 977 genes, indicating substantial effects on cell differentiation. Genes related to cell migration, including the gut homing integrin gene ITGB7, were decreased, whereas genes related to cytokine production were increased. Conclusions: TRPM8 is expressed in human blood and intestinal monocyte populations where it has constitutive activity that modulates the transition into macrophages and limits inflammation. Understanding alterations in this pathway in IBD may allow identification of novel therapeutic targets.